1993
DOI: 10.1016/0741-5214(93)90606-m
|View full text |Cite
|
Sign up to set email alerts
|

Should the Cell Saver Autotransfusion Device* be used routinely in all infrarenal abdominal aortic bypass operations?

Abstract: We conclude that routine setup and use of rapid autotransfusion devices may not be necessary in every patient undergoing routine aortofemoral bypass for occlusive disease. Furthermore, the possibility that some patients may undergo AAA repair with tube grafts without use of the Cell Saver may be deserving of further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In vascular surgery, data on the efficacy of ICS have been contradictory. Although there have been many retrospective [29][30][31][32][33][34] and prospective 18,[35][36][37][38] studies investigating the role of cell salvage in aortic surgery, until recently, only three prospective randomized controlled trials had been reported. [39][40][41] In the largest of the three, Clagett et al 41 randomized 100 patients undergoing infrarenal aortic reconstruction to ICS or standard transfusion practice with allogeneic blood when needed.…”
Section: Does Ics Reduce Allogeneic Blood Use?mentioning
confidence: 99%
“…In vascular surgery, data on the efficacy of ICS have been contradictory. Although there have been many retrospective [29][30][31][32][33][34] and prospective 18,[35][36][37][38] studies investigating the role of cell salvage in aortic surgery, until recently, only three prospective randomized controlled trials had been reported. [39][40][41] In the largest of the three, Clagett et al 41 randomized 100 patients undergoing infrarenal aortic reconstruction to ICS or standard transfusion practice with allogeneic blood when needed.…”
Section: Does Ics Reduce Allogeneic Blood Use?mentioning
confidence: 99%
“…8,12 Neither study demonstrated a clinically important decrease in the number of patients exposed to red cells following the use of cell salvage. The Clagett study reported a RR of 0.94 (95% CI from 0.63 to 1.40) and the Kelley-Patteson study reported a RR of 1.50 (95% CI from 0.28 to 7.93).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…8,12 This surgical intervention requires significantly less RBC transfusions as compared to aortic aneurysm surgery. Both major studies 8,12 evaluating cell salvage during aortofemoral bypass were not able to document any savings in allogeneic RBC use with this technique. Inferences from these studies and the resultant meta-analysis are weak given the small sample size of both individual studies and the pooled results.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
See 2 more Smart Citations